2002
DOI: 10.1200/jco.20.6.1551
|View full text |Cite
|
Sign up to set email alerts
|

Role of P53 and MDM2 in Treatment Response of Human Germ Cell Tumors

Abstract: Although our results are in line with previous findings of the presence of wild-type P53 in TGCTs, they show that a high level of P53 does not relate directly to treatment sensitivity of these tumors, and inactivation of P53 is not a common event in the development of cisplatin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
68
0
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 0 publications
8
68
0
2
Order By: Relevance
“…Most of the genes analysed, however, were either not detectable (no signal) or only weakly expressed in NCCIT cells (weak signals) and did not reveal any down-or upregulation after drug treatment. p53, the p53-regulated gene mdm-2 and genes from the Bcl-2 family belonged to this group, as reported by others (Burger et al, 1997;Kersemaekers et al, 2002) (Table 1). The expression level of five genes including IGFBP-2, AP-1, CDC25A, GADD45 and ID-1 was decreased in treated cells compared to the levels in untreated cells (Table 1).…”
Section: Analysis Of Apoptosis-regulating Genes Following Cddp Treatmentsupporting
confidence: 81%
See 1 more Smart Citation
“…Most of the genes analysed, however, were either not detectable (no signal) or only weakly expressed in NCCIT cells (weak signals) and did not reveal any down-or upregulation after drug treatment. p53, the p53-regulated gene mdm-2 and genes from the Bcl-2 family belonged to this group, as reported by others (Burger et al, 1997;Kersemaekers et al, 2002) (Table 1). The expression level of five genes including IGFBP-2, AP-1, CDC25A, GADD45 and ID-1 was decreased in treated cells compared to the levels in untreated cells (Table 1).…”
Section: Analysis Of Apoptosis-regulating Genes Following Cddp Treatmentsupporting
confidence: 81%
“…Although Chresta et al (1996) postulated that a hypersensitivity of human TGCT to drug-dependent apoptosis may also be associated with functional p53 , Burger et al (1999) showed that abrogation of the p53 function does not affect the hypersensitivity of human TGCT cell lines to chemotherapy. Thus in human TGCT, apoptotic signalling pathways including those activated by CDDP seem to be -at least partly -p53 independent (Burger et al, 1997;Kersemaekers et al, 2002).…”
mentioning
confidence: 97%
“…Chemoresistance has been linked to P53 gene mutations by some investigators 14 but not others. 15 By comparative genomic hybridization analysis, Rao et al 16 identified possible amplified regions involving multiple chromosomes (1q, 2p, 7q, 9q, 9q, 15q, and 20q) in cisplatin-resistant germ cell tumors. Identification of amplified/overexpressed genes may elucidate genetic pathways of chemotherapy resistance in germ cell tumors and may help in the development of novel treatments targeted at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…One of the unsolved issues in the pathogenesis of type-II GCTs is the overall presence of wild-type P53 protein [74][75][76] , the most frequently inactivated gene in solid cancers. 77 The requirement to inactivate P53 is (partly) due to the role the P53 protein plays in overruling the mechanism of cellular senescence, induced for example by oncogenic stress.…”
Section: Additional Malignant 'Intrinsic' Characteristics Of Embryonimentioning
confidence: 99%